Phospho sulfonic acid: an efficient and recyclable solid acid catalyst for the solvent-free synthesis of α-hydroxyphosphonates and their anticancer properties. (17th March 2015) - Kalla, Reddi Mohan Naidu; Lee, Hye Ri; Cao, Jiafu; Yoo, Jin-Wook; Kim, Il
Abstract : Some of the title compounds synthesized by a green protocol showed potent anticancer activity. Abstract : As a means of developing biologically active compounds, a series of α-hydroxyphosphonates, ArC(OH)PO(OR)2 (Ar = 5-G-2-OHPh; R = Me, Et, iPr, Bu; G = H, Br, Cl, NO2 ), have been synthesized by reacting diversely substituted salicylaldehydes with dialkyl phosphites by employing the Pudovik reaction in the presence of phospho sulfonic acid under neat conditions. The cytotoxicity of the compounds was tested in two human cancer cell lines by using MTT assay. Compounds bearing R = Et; G = Cl, R = Bu; G = Cl, and R = Et; G = NO2 showed good anticancer activity.